"More sidewalks, more bus stops": Travel behaviors and opinions of Connecticut teenagers. (November 2020) - Auguste, Marisa E.; Tucker, Andrew; Jackson, Eric D.
Abstract: An online survey was developed to evaluate the environmental, demographic, and socioeconomic factors that support or discourage the mobility of teenagers. Distributed to adults (18–25 years old) in Connecticut, the survey gathered retrospective data on their travel behaviors as teenagers, as well as associated attitudes and beliefs about different transportation modes. Seventy-one percent of participants indicated that a family car was their predominant source of transportation. Public transportation was the main source for 14% of participants. Fewer than 10% of participants indicated that a personal car, walking, or other means was their primary source of transportation. Participants who lived in less densely populated areas as teenagers were more likely to report barriers to public transportation access. These same participants were also more likely to report neighborhood walkability issues, including the absence of continuous sidewalks and bike paths. These factors are likely associated with teenagers' reliance on family cars for transportation. Recommendations for improved connectivity and promotion of currently available public transportation options are provided. Highlights: Mobility issues of teens, an understudied topic, were examined via online survey. Adolescents from low-income households and rural areas face specific challenges. Many respondents raised issues of accessibility, walkability, and safety. Socioeconomic status and population size affect travel behavior and mobility. Highlights the need for greater connectivity in state transportation planning